PENGARUH LATIHAN MEMUKUL BOLA GANTUNG TERHADAP KETEPATAN SMASH BOLA VOLI - Ridwan Sinurat; Riwaldi Putra; Helka Permata Yolanda (Jurnal Muara Pendidikan, 2023)
This research started from the observations of researchers in the field who shaw that the smash ability of extracurricular students at MTs Bahrul Ulum was still low. For this reason, this study aims to determine the effect of the Hanging Ball Hitting Exercise as an independent variable (X) on the result of smash accuracy as the dependent variable (Y). This study uses an experimental method with On Group Pre-test and Post-test Design, the sampling technique uses Saturated Samples so that the number of samples consists of 12 male genders. The research design uses Pre-test and Post-test using the Smash test instrument to determine the results of students’ smash accuracy. Data analysis techniques with a significant level of a = 0.05. The results showed that the Hanging Ball Hitting Practice had an effect on the accuracy of the smash with an average score of 4.7 on the Pre-test increasing to 2.55 I the Post-test. The statistical results show that (tcount 6,740 > ttables 1,769). The conclusion of this study is the Hanging Ball Hitting Exercise affects the accuracy of the results of the Smash extracurricular students of MTs Bahrul Ulum.